Design and Experimental Study on Shock-Absorbing Steel Bar with Limit Function for Bridges - Zhaoguang Li; Ri Gao; Wei Jia (Shock and Vibration)
The existing research on shock-absorbing steel bars is only limited to simply supported beam bridge. In order to expand the application of shock-absorbing steel bars to other fields, this paper develops a novel shock-absorbing steel bar with limit function, and it is suitable for continuous beam bridges. The structure and working mechanism of the shock-absorbing steel bar are analyzed. Three sets of specimens of the shock-absorbing steel bar are fabricated and then repeatedly loaded by the designed quasistatic loading device, in order to investigate their seismic performance parameters, including hysteresis curve, skeleton curve, and initial stiffness and equivalent viscous damping ratio. The results show that when the displacement of the specimen exceeds the initial gap, it enters the stage of energy dissipation and has a stable hysteresis curve and good fatigue resistance. Besides, the shock-absorbing device has a high initial stiffness and can provide stable bearing capacity after yielding. The equivalent viscous damping ratio reflects that the designed shock-absorbing steel bar has good energy dissipation capacity.